BLS Training on The Application of BLS and The Standard Operational Procedures First AID on Emergeny Tourism at Tanjung Karang Beach Donggala District - Ndama, Metrys; Umar, Nurlailah; Ismunandar, Ismunandar (Poltekkes Kemenkes Palu, 2023)
Indonesia is an archipelago consisting of around 17,508 islands, 70% of which are oceans. Indonesia's seas are rich in natural resources, including coral reefs and marine animals. However, this natural wealth can cause problems and is fatal to humans due to stings from animals in the sea. In other emergency conditions, people can drown, causing suffocation and heart attacks. First aid in emergencies is basic life support (BLS), which can be done by people who have received training. Tanjung Karang Beach is a domestic and international tourist destination; however, health services and experts in providing BLS are not yet available. The data from 2015 to 2022 reported the occurrences of tourist vehicle accidents, tourists were stung by Marlyn fish stabs, and the incident of people drowning resulted in death without emergency action. This study aimed to determine the effect of BLS training on applying BLS and standard operational procedures in emergency first aid. The research method was a quasi-experimental pretest and posttest group design. The population was lifeguards and tourist vehicle drivers, with samples taken purposively. The measurement of the application of BLS was carried out twice: before and after training. Data analysis used univariate and bivariate analyses. The results showed a mean value before training was 1.37, with a standard deviation was 0.684. The mean value after training was 14.63, and the standard deviation was 1.383. The dependent T-test results were 13.263, and the standard deviation was 1.327, with a p-value of 0.000 (p<0,005). The conclusion is that BLS training affects the application and operational standards of BLS training. Training members are recommended to apply for BLS in caring for the victims, and the Donggala Regency Government is to organize a tourist clinic in Tanjung Karang Beach and empower training personnel as rescuers.